Cotton gauze bandage: a support for protease immobilization for use in biomedical applications (Revista Brasileira de Ciências Farmacêuticas, 2007)
The covalent immobilization of trypsin on sterilized cotton gauze bandage was carried out for future use as an anti-inflammatory agent on wound dressing. The optimal immobilization conditions were determined: the influence of pH, concentration, and volume of the trypsin solution used in the immobilization procedure was studied. The catalytic properties and kinetic parameters, as well as the storage stability of the immobilized and free enzyme were compared. Results showed that the optimal pH and temperature for the immobilized trypsin in the hydrolysis of N-benzoyl-DL-arginine p-nitroanilide were 9.5 and 55 ºC, which were higher than those of the free form (7.5 and 45 ºC). It was found, at 37 ºC and pH 7.0 (approximately, the physiological conditions), that the Km (Michaelis constant) was 3.98 µmol/mL and that Vmax (maximal reaction rate) was 0.719 µmol/(min mg) for the immobilized trypsin, compared to a Km of 2.46 mmol/mL and a Vmax of 2.89 µmol/(min mg) for the free trypsin. The amount of immobilized trypsin was 6 mg/g dried support. After 30 days, no trypsin had liberated from the support. The superior performance of the immobilized trypsin demonstrates its potential application in practice.